2008
DOI: 10.1002/jctb.1878
|View full text |Cite
|
Sign up to set email alerts
|

Influence of light quality and intensity in the cultivation of Spirulina platensis from Toliara (Madagascar) in a closed system

Abstract: International audienceBACKROUND: Spirulina platensis (Toliara, Madagascar) provides a food supplement which can fight against malnutrition and food insufficiency in Madagascar. In this country, the current production from three open basins is not sufficient to cover needs, and presents drawbacks such as low productivity and possible contamination. Thus cultivation of S. platensis in a closed photobioreactor opens the possibility of extending this microalga production. In this study, the influence of colour and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 34 publications
1
45
0
Order By: Relevance
“…). Ravelonandro et al (2008) reported that green light was better for accumulation of A. platensis biomass than the other light qualities studied (white, red, and blue). However, the results obtained in the present study are quite different; they indicate that white light promotes more biomass accumulation than green light.…”
Section: Arthrospira Platensis Growth Under Different Cultivation Conmentioning
confidence: 87%
See 3 more Smart Citations
“…). Ravelonandro et al (2008) reported that green light was better for accumulation of A. platensis biomass than the other light qualities studied (white, red, and blue). However, the results obtained in the present study are quite different; they indicate that white light promotes more biomass accumulation than green light.…”
Section: Arthrospira Platensis Growth Under Different Cultivation Conmentioning
confidence: 87%
“…Another study showed a higher content of protein in biomass cultivated under white and green light-emitting diode (LED) compared with that obtained under blue, yellow, red, and pink LED (Markou, 2014). Ravelonandro et al (2008), found a protein content value of 58% in S. platensis after 10 days of growth under green light at irradiance 1200 lux (~17 μmol fotons.m ). In the present study, the protein content obtained was 59% after 18 days of growth under green light at irradiance of 50 μmol fotons.m -2 .s -1 green light.…”
Section: Total Protein Contentmentioning
confidence: 98%
See 2 more Smart Citations
“…Studies have also suggested that growth under red light (600-700 nm) enhanced PSII relative to PSI, whereas blue light (400-500 nm) could induce PSI. These findings suggest that blue and red lights are more suitable than others for both microalgal cell growth and CO 2 mitigation (You and Barnett 2004;Ravelonandro et al 2008).…”
Section: Propagation Systemsmentioning
confidence: 81%